Exploring the potentials of urban crop farming and the question of environmental sustainability - Alfred Toku; Samuel Twumasi Amoah; Nelson Nyabanyi N-yanbini (City and Environment Interactions)
As part of efforts to promote urban green spaces in increasingly urbanized cities of Africa, urban crop farming (UCF) has become a necessary pillar of urban environmental sustainability. Beyond the primary functions of food security and employment, UCF contributes to greening the urban environment and provides valuable options for urban regeneration within the broad components of environmental, social, and economic sustainability. We draw on interviews and focus group discussions in Tamale, a rapidly urbanizing Ghanaian metropolis, to examine the potential of UCF and the question of urban environmental sustainability. Our findings revealed the tremendous contributions of UCF to the provision of greenery, beautiful scenery, healthy spaces, socio-economic inclusion, and environmental restoration. We argue that reflecting and incorporating these findings in policy will be helpful for urban landscape planning and management.